Pendekatan Solution Focused Brief Counseling Dalam Konseling Pastoral Mengatasi Kecemasan - Laura Meirien Olivia Pangayow; Juliana Hindradjat (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2026)
Anxiety is a multidimensional psychological phenomenon, encompassing emotional, cognitive, physical, and spiritual aspects. In psychology, anxiety is understood as an adaptive response to life's pressures, but it can develop into a disorder if it hinders an individual's functioning. Meanwhile, Christian theology views anxiety not only as a psychological issue, but also as something related to human relationships with God, the meaning of life, and dependence on faith. Therefore, Christian pastoral counselling is seen as a relevant holistic approach to dealing with anxiety. This study aims to examine the application of Christian pastoral counselling with a Solution-Focused Brief Counselling (SFBC) approach in helping individuals overcome anxiety. The method used is library research by reviewing books and scientific articles that discuss anxiety, pastoral counselling, and SFBC. The analysis was conducted systematically to obtain a comprehensive theoretical understanding. The results of the study indicate that the integration of SFBC in pastoral counselling is effective in helping counselees to concretise their anxiety problems, recognise their spiritual strengths and resources, and build hope oriented towards recovery. The SFBC approach, which focuses on solutions and the future, is in line with Christian theological values that emphasise hope, restoration, and God's presence. It is concluded that SFBC-based pastoral counselling is an applicable and theological approach to treating anxiety holistically.